PROFILE OF NEGATIVE AUTOPSY CASES AT PUNJAB MEDICAL COLLEGE, FAISALABAD - Altaf Pervez Qasim; Saeed Akbar Tariq; Perwaiz Ahmed Makhdoom et al. (Journal of University Medical & Dental College, 2015)
ABSTRACT: BACKGROUND: One of the most frustrating challenges faced by the medico legal doctors / forensic pathologists is the inability to determine the cause of death in cases of sudden / unexpected deaths of medicolegal nature even after detailed autopsy as well as Histopathalogical / Toxicological analysis. OBJECTIVE: The study was aimed to find out the percentage of negative autopsy against the total cases of medicolegal autopsies conducted during the study period. MATERIAL AND METHODS: The study was carried out in the Department of Forensic Medicine & Toxicology, Punjab Medical College Faisalabad and was based upon five years autopsy data from 1st January 2006 to 31st December 2010. All the medicolegal autopsies conducted by the demonstrators of Forensic Medicine Department were included in the study whereas; the cases of alleged custodial deaths / police encounters and autopsies conducted by the District Standing Medical Board (DSMB) were excluded. The cases where gross examination at initial autopsy, histopathalogical examination & toxicological analysis failed to detect the cause of death were labeled as negative autopsies. STUDY DESIGN: Retrospective Study. SETTING & DURATION: The study was conducted in Forensic Medicine Department of Punjab Medical College Faisalabad; for a period of five years from 1st January, 2006 to 31st December, 2010. RESULTS: Out of the total 1681 autopsies, 1298 (77.22%) were males and 383 (22.78%) were females. After conducting detailed autopsy, histopathologic examination as well as toxicological analysis; 155 (9.22%) cases were found to be negative. The highest percentage of negative autopsy (12.30%) was found in year 2009 while average percentage of negative autopsy was 9.22%. Among the total 155 cases, the percentage of negative autopsy in males 119 (76.77%) was higher than females 36 (23.23%). The age of deceased ranged from 8 – 73 years. Majority i.e. 51 (32.90%) were in the age range of 20-29 years, followed by 38 (24.51%) in the age range of 30-39 years. Twenty nine (18.71%) cases were in the age range of 40-59 years and 21 (13.54%) cases belonged to the age group of 0-19 years. Among these negative autopsies, 92 (59.35%) belonged to the urban community and 63 (40.65%) were inhabitants of rural areas of Faisalabad. Majority of negative autopsies were of young adults from urban areas.